Narratives and practices of environmental justice - Hein, Jonas; Dünckmann , Florian (DIE ERDE – Journal of the Geographical Society of Berlin, 2020)
This editorial provides an overview of the roots of environmental justice movement and scholarship. It identifies emerging frontiers of environmental justice research and introduces the contributions of this special issue. Finally, we call for further research on the role of the state in environmental justice struggles and for more participatory methodologies in environmental justice research.